Behavioral responses of the pampas deer (Ozotoceros bezoarticus) to human disturbance in San Luis province, Argentina - Semeñiuk, María Belén (2016)
Pampas deer (Ozotoceros bezoarticus, Linnaeus 1758) is a South American cervid, associated with grasslands and savannas; in Argentina this species is listed as “endangered”. Our aim was to analyze the behavioral responses of the pampas deer to human presence, and to evaluate possible effects of their poaching. We recorded behavioral responses from 382 pampas deer groups during eight vehicle surveys, in “El Centenario” ranch (San Luis Province). Data were analyzed using the G-test of independence and logistic regression. Almost half of the groups (48.17 percent) remained on site. Behavioral responses differed significantly according to group size and composition and observer distance; being this last the variable most influencing flight, groups were more likely to flee at shorter distances. In return, behavioral responses were independent from habitat type, transect type and season. Our results suggest certain human tolerance and that consequently, poaching would not have important effects on this population.